Advances in immunology in China : Part A - Dong, Chen; Jiang, Zhengfan (Advances in immunology, 2019)
"Advances in Immunology in China - Part A, Volume 144, the latest release in the Advances in Immunology series, presents the latest release in a long-established and highly respected publication. The book includes current developments and comprehensive reviews in immunology. Articles address the wide range of topics that comprise immunology, with this release focusing on advances in immunology in China."--Publisher's web page, viewed November 7, 2019